Clinicopathological analysis of oral mucous autoimmune disease: A 27-year study - Arisawa, Emília Angela Loschiavo; Almeida, Janete Dias [UNESP]; Carvalho, Yasmin Rodarte [UNESP]; Cabral, Luiz Antonio Guimarães [UNESP] (My University, 2008)
Objectives: The aim of the present study was to analyze the main clinical and histopathological features of autoimmune diseases with oral manifestations such as oral lichen planus (OLP); mucous membrane pemphigoid (MMP); pemphigus vulgaris (PV) and erythema multiforme (EM). Study design: Retrospective review of 5770 files from the Oral Pathology Laboratory of São José dos Campos Dental School, São Paulo State University (UNESP) comprising a 27-year period from 1974 to 2000. Results: The cases accounted for 64 (1.10%) of 5770 anatomopathological examinations performed over the study period. Among the autoimmune diseases diagnosed, 49 (76.56%) were OLP, 6 (9.37%) were MMP, 5 (7.82%) were EM and 4 (6.25%) were PV. Descriptive statistical analysis was used. Conclusion: The initial manifestations of most autoimmune diseases occur in the oral mucosa. An earlier diagnosis and proper therapeutic protocol will delay the dissemination of the lesions, thus greatly contributing to a better prognosis and quality of life of the patient. © Medicina Oral S. L.
Keywords: Autoimmune diseases; Erythema multiforme; Lichen planus; Mucous membrane; Pemphigoid; Pemphigus